Comparison Between Eddy‐Covariance and Flux‐Gradient Size‐Resolved Dust Fluxes During Wind Erosion Events. Issue 13 (28th June 2021) - Dupont, S.; Rajot, J.‐L.; Lamaud, E.; Bergametti, G.; Labiadh, M.; Khalfallah, B.; Bouet, C.; Marticorena, B.; Fernandes, R.
Abstract: Estimating accurately dust emission flux during aeolian erosion events is crucial for quantifying the amount of dust in the atmosphere. The rare existing field experiments quantifying such flux were mainly performed using the flux‐gradient (FG) method. Here, we present the first intercomparison of the size‐resolved dust fluxes estimated by both the FG and the eddy‐covariance (EC) methods during several erosion events. Both methods were applied simultaneously during the WIND‐O‐V (WIND erOsion in presence of sparse Vegetation)'s 2017 field experiment over an isolated erodible bare plot in South Tunisia. Overall, both methods predict similar dust fluxes for particle smaller than about 4 μm. For coarser particles, the EC method predicts a smaller dust flux than the FG method. Factors explaining this difference are discussed such as the different sampling heads used by the dust particle counters of both methods, or the possible weakening of the constant dust flux layer at the location of the upper dust particle counter of the FG method. This intercomparison highlights the difficulties and advantages of each method as well as their complementarity. Key Points: For the first time, the flux‐gradient method used to estimate size‐resolved dust fluxes is compared to the eddy‐covariance method Both methods lead overall to similar dust fluxes. Differences are discussed, highlighting the difficulties and advantages of each method The EC method, rarely applied in aeolian soil erosion research, appears promising